Respon guru terhadap pelatihan pembuatan media pembelajaran berbasis TIK di Benteng Kepulauan Selayar - ani Kurnia; Adnan Adnan; Hamka L; Syamsul Bahri Hs (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This devotion was carried out at SMP Negeri 1Benteng Kep. Selayar and attended by teachers in Benteng andSelayar Islands Senior High School and Senior High School inorder to improve understanding, skills, and innovation inpreparing evaluation questions using the Wondershare QuizCreator program. In this Community Partnership programtraining activities have been conducted to create interactiveICT-based questions. The results obtained from these programactivities are responses of all participants who have been ableto compile interactive questions that are innovative and variedindependently so that a varied and enjoyable evaluationactivity will be formed. Another advantage is that the teachercan make interactive computer-based questions.